Novel participant-level meta-analytic evidence for AbSANT efficacy - Sandberg, Chaleece W.; Khorassani, Hannah; Gray, Teresa; Dickey, Michael Walsh (Frontiers in Rehabilitation Sciences, 2023)
The current study employed interrupted time series (ITS) models to analyze all available (published and unpublished) Abstract Semantic Associative Network Training (AbSANT) data. AbSANT is a semantically focused anomia treatment that targets not only concrete but abstract words, unique among existing anomia treatments. However, evidence to date for the positive effects of AbSANT comes only from small-sample, single-subject design studies, limiting the strength of this evidence and the inferences that can be drawn from it. The statistical power and greater representativeness afforded by this larger aggregated sample enabled us to look for group-level efficacy evidence for AbSANT, examine specific questions about AbSANT's direct training and generalization effects, and identify potential predictors and mechanisms of AbSANT treatment response. We found that across 33 participants from four different data sources, AbSANT appears to be a robust word retrieval therapy protocol, with overall direct training and generalization effects that were more meaningful than exposure effects. Similar to previous smaller-sample study conclusions, we found that in this large sample, training abstract words results not only in larger direct training effects than training concrete words, but also larger generalization effects, suggesting that while AbSANT successfully improves both abstract and concrete word retrieval, it may be better suited for training abstract words. In general, direct training effects were more persistent after treatment ended than generalization effects and effects for concrete words were more persistent than for abstract words. Additionally, the effects of generalization appear to be distinct from the effects of simple exposure to words, and generalization effects are consistent with AbSANT's hypothesized mechanism of action: spreading activation from directly trained concepts to related concepts. Also consistent with this mechanism, we found that milder aphasia and both conceptual and lexical semantic processing ability predicted both direct training and generalization gains, and that executive function was predictive of